2013
DOI: 10.1016/j.cca.2013.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of anti-platelet therapy focused on peripheral blood cells of coronary arterial disease patients

Abstract: The variation in response to ASA may be related with an increased expression of IGF1 and IGF1R, as well as a response to clopidogrel can be affected by pharmacokinetic change related to the reverse transport pathway by increased expression of ABCC3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, catecholamines such as epinephrine can also act as platelet primers when used at suboptimal concentrations . Interestingly, recent pharmacogenomics studies have also linked increased expression of IGF‐1 and IGF‐1 receptor mRNA with ASA resistance . Furthermore, coronary heart disease (CHD) patients have been found to have significantly higher serum concentrations of IGF‐1, a feature that is believed to contribute to coronary atherosclerosis .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, catecholamines such as epinephrine can also act as platelet primers when used at suboptimal concentrations . Interestingly, recent pharmacogenomics studies have also linked increased expression of IGF‐1 and IGF‐1 receptor mRNA with ASA resistance . Furthermore, coronary heart disease (CHD) patients have been found to have significantly higher serum concentrations of IGF‐1, a feature that is believed to contribute to coronary atherosclerosis .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ABCC3 mRNA expression may be useful for clopidogrel monitoring in ACS patients. We previously reported that ACS patients with elevated ABCC3 mRNA expression did not respond to clopidogrel therapy , supporting the relationship between high CAM concentrations and high platelet activity as well as increased ACS risk. However, we cannot rule out the influence of other therapies used in the treatment of ACS patients, including clopidogrel and ASA, on ABCC3 regulation in peripheral blood cells.…”
Section: Discussionmentioning
confidence: 52%
“…Limma package () in R (version 3.5.1; ) was used to identify differentially expressed lncRNAs and mRNAs among the asthma and control groups via a t-test (18). Fold change (FC)>1.2 and P<0.05 were set as the criteria for differential expression (19). Hierarchical clustering was conducted in R scripts.…”
Section: Methodsmentioning
confidence: 99%